ANALYSIS OF THE INFLUENCE OF BRAND IMAGE, PRODUCT QUALITY AND PRICE PERCEPTION ON THE PURCHASE DECISION OF HONDA MOTOR VEHICLES IN WEST HALMAHERA - Gabriel Sylvian Frans Ofa; Dewi Wuisan (Universitas Pelita Harapan, 2021)
Destination study this is for analyze influence image brand, quality product, and perception price to the decision process purchase consumer Honda automatic motorcycle in West Halmahera. Population in study this is user Honda automatic motorcycle. Taking sample in study this using purposive sampling use approach quantitative with method collection use questionnaire electronic via Google Forms. Measurement models and structural models in study this analyzed with use SmartPLS 3.0. Respondent in study this is West Halmahera community as many as 160 respondents. Analysis result could conclud that: Brand image take effect positive to the decision process purchase consumer Honda automatic motorcycle in West Halmahera. Quality Product no take effect positive to the decision process purchase consumer automatic motorcycle Honda in West Halmahera. And Perception price take effect positive to the decision process purchase consumer Honda automatic motorcycle in West Halmahera.BAHASA INDONESIA ABSTRACTTujuan penelitian ini adalah untuk menganalisis pengaruh citra merek, kualitas produk, dan persepsi harga terhadap proses keputusan pembelian konsumen sepeda motor matic Honda di Halmahera Barat. Populasi dalam penelitian ini adalah pengguna sepeda motor matic Honda. Pengambilan sampel dalam penelitian ini menggunakan purposive sampling menggunakan pendekatan kuantitatif dengan metode pengumpulan menggunakan kuesioner elektronik melalui Google Forms. Model pengukuran dan model strukturl dalam penelitian ini dianalisis dengan menggunakan SmartPLS 3.0. Responden dalam penelitian ini adalah masyarakat Halmahera Barat sebanyak 160 responden. Hasil analisis dapat disimpulkan bahwa: Citra merek berpengaruh positif terhadap proses keputusan pembelian konsumen sepeda motor matic Honda di Halmahera Barat. Kualitas Produk tidak berpengaruh positif terhadap proses keputusan pembelian konsumen sepeda motor matic Hondadi Halmahera Barat. Serta Persepsi harga berpengaruh positif terhadap proses keputusan pembelian konsumen sepeda motor matic Honda di Halmahera Barat.